THE DEVELOPMENT OF DIGITAL TEACHING MATERIALS WITH PROBLEM-BASED LEARNING ON THE AMPHIBIA SUBJECT TO IMPROVE STUDENTS COMMUNICATION SKILLS - Saritha Kittie Uda; Septika Yantie; Shanty Savitri (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2022)
The restrictions on social contact due to the Covid-19 pandemic also impacted the education sector causing many learning activities being carried out online. This research aims to 1) produce designs, 2) determine the feasibility level, and 3) determine the results of the development of problem-based learning digital teaching materials using Amphibia class subject materials in order to improve students’ communication skills. This research is development research using the ADDIE model with data collection techniques through interviews, validation, response questionnaires, observation of communication skills, and tests. Validation result data and response questionnaires were analyzed with the formula of eligibility criteria, respondent criteria and the N-Gain test. The analyses of the results show that the digital teaching materials produced are in the